Javanese Society's Eyes: Understanding Phenomenon of People with Mental Disorders in Java - Dumpratiwi, Ajeng Nova; Cahyadi, Maskuri Muhammad; Ardani, Alvanindya Nafik (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Society has various beliefs, one of which is related to mental disorders. Many people's beliefs are still wrong in understanding mental disorders, and causes society to treat people with mental disorders (Orang Dengan Gangguan Jiwa/ODGJ) inappropriately. People who misunderstand mental disorders will usually take inhumane actions such as alienating survivors or taking other actions that worsen the mental condition of survivors. This research explored the attitudes and perspectives of Javanese people in understanding mental disorders. The ultimate goal is to provide theoretical contributions that bridge scientific definitions and assumptions that are believed in the local community's perspective regarding mental disorders. In accordance with the research objective, this research used a descriptive qualitative approach, involving 98 respondents in a semi-structured interview. Respondents were selected based on characteristics called